Meditasie: Bybelgefundeerd of "n vermenging van gelowe? "n Pastorale ondersoek - Plessis, Amanda L. du (HTS teologiese studies, 2013)
Meditation: Bible based or a mix of religion? A Pastoral investigation. The influence of other religions on the Christian community was a perceptible trend that cannot be ignored in the realm of spirituality. Meditation was one such example and consequently requires thoughtful investigation. Some Christians found meditation a valuable spiritual discipline that aids their spiritual growth but, in my opinion, also opened up the door for them to become victims of a subtle spiritual deception. The question posed was: how can Christians distinguish between the many and often-conflicting views on meditation found in easily accessible literature? A need therefore exists to define meditation as a possible Christian spiritual expression by distinguishing its uniqueness from the influences of other non-Christian religions and popular opinion.